Validity and utility of four pain intensity measures for use in international research - Raviwon Atisook (2022)
Background: The majority of previous research that has examined the validity of pain intensity rating scales has been conducted in western and developed countries. Research to evaluate the generalizability of previous findings in non-developed countries is necessary for identifying the scales that are most appropriate for use in international research. Purpose: The aims of the current study were to (1) evaluate the validity and utility of four commonly used measures of pain intensity in a sample of patients with chronic pain from Thailand and (2) compare findings in the current sample with published findings from research conducted in other countries, in order to identify the measure or measures which might be most appropriate for cross-country research. Methods: Three hundred and sixty patients with chronic pain seen in a hospital in Bangkok, Thailand, were asked to rate their current pain and average, worst, and least pain intensity in the past week using the Visual Analogue Scale (VAS), 6-point Verbal Rating Scale (VRS-6), 0–10 Numerical Rating Scale (NRS-11), and Faces Pain Scale-Revised (FPS-R). We evaluated the utility and validity of each measure by examining the (1) rates of correct responding and (2) association of each measure with a factor score representing the variance shared across measures, respectively. We also evaluated the associations between incorrect response rates and both age and education level, and then compared the findings from this sample with the findings from research conducted in other countries. Results: The results indicated support for the validity of all measures among participants who were able to use these measures. However, there was variability in the incorrect response rates, with the VAS having the highest (45%) and the NRS-11 having the lowest (15%) incorrect response rates. The VAS was also the least preferred (9%) and the NRS-11 the most preferred (52%) scale. Education and age were significantly associated with incorrect response rates, and education level with scale preference. Conclusion: The findings indicate that the NRS-11 has the most utility in our sample of Thai individuals with chronic pain. However, when considered in light of the findings from other countries, the results of this study suggest that the FPS-R may have the most utility for use in cross-cultural and international research. Research in additional samples in developing countries is needed to evaluate the generalizability of the current findings.